7x+9=2x+29

Simple and best practice solution for 7x+9=2x+29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+9=2x+29 equation:


Simplifying
7x + 9 = 2x + 29

Reorder the terms:
9 + 7x = 2x + 29

Reorder the terms:
9 + 7x = 29 + 2x

Solving
9 + 7x = 29 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
9 + 7x + -2x = 29 + 2x + -2x

Combine like terms: 7x + -2x = 5x
9 + 5x = 29 + 2x + -2x

Combine like terms: 2x + -2x = 0
9 + 5x = 29 + 0
9 + 5x = 29

Add '-9' to each side of the equation.
9 + -9 + 5x = 29 + -9

Combine like terms: 9 + -9 = 0
0 + 5x = 29 + -9
5x = 29 + -9

Combine like terms: 29 + -9 = 20
5x = 20

Divide each side by '5'.
x = 4

Simplifying
x = 4

See similar equations:

| ln(x)=ln(27)+ln(15)+ln(36) | | -8+4(1+5n)=-6n+14 | | m^2-12m=0 | | 3y(3y-1)-3(2y)=2 | | 0.35x+0.05(12-x)=0.10(0) | | c+4=56 | | 3n+6.5=21.5 | | 4w=w+12 | | x(x+17)=-72 | | f(x)=ln(7) | | q+26=29 | | 7x+8=8x+20 | | 541x-64=-803 | | 6x-2(-5x-7)=-98 | | 2s=s+23 | | 3-4(x+2)=x-10 | | c-5=20 | | 4x-6=x+3(x-5) | | 6z^3-13z^2+6z=0 | | m^3-36m=0 | | (x-5)(-5)=0 | | 3x-3+45=-3x | | -6x+6(7x-15)=198 | | 6(5x+1)=5x-8X | | 3(4x+3)=2-5(7-x) | | 164x-82=738 | | 7(3x+1)=3x-8x | | 0.02x+0.5=0.35x+1.2 | | 5x+1=-13x+15 | | 2z+96=15z-85z | | 21x^2=7x | | x^2+2i=0 |

Equations solver categories